Scale economies, bank mergers, and electronic payments: A spline function approach - Humphrey, David B; Vale, Bent (Journal of Banking & Finance, 2004)
This paper demonstrates the importance of using a flexible cost function specification when analyzing economies of scale and estimating the cost effect of banking mergers. The inflexibility of the translog cost function is illustrated and results are compared to more flexible spline and Fourier cost functions. Using these different approaches we predict the ex ante effect on average cost from mergers over 1987–1998 using a balanced panel of 130 Norwegian banks. On average mergers are predicted to lower costs. Predictions using the Fourier or spline approach are in overall agreement with computed actual average merger-cost changes ex post. Cost effects of electronic payments are also estimated and exceed cost reductions associated with mergers.